Necessary Optimality Conditions for a Class of Impulsive and Switching Systems - Lihua Li; Yan Gao; Gexia Wang (Journal of Applied Mathematics)
An optimal control problem for a class of hybrid impulsive and switching systems is considered. By defining switching times as part of extended state, we get the necessary optimality conditions for this problem. It is shown that the adjoint variables satisfy certain jump conditions and the Hamiltonian are continuous at switching instants. In addition, necessary optimality conditions of Fréchet subdifferential form are presented in this paper.